Dynamics of Gravity Currents in the Presence of Surface Waves. Issue 3 (30th March 2018) - Stancanelli, L. M.; Musumeci, R. E.; Foti, E.
Abstract: The gravity current dynamics in the presence of regular surface waves is investigated experimentally. The aim is to determine the influence of the wave‐induced velocity field on gravity current kinematic parameters and on the concentration distribution. In the presence of surface waves, the front shows a pulsating behavior while periodic oscillations are observed at the interface between lighter and denser fluids. The dynamics of such processes is related to the wave parameters. Present results confirm that the lock‐exchange generated front velocity is strongly influenced by the oscillatory motion and it may be increased or decreased depending on the Lagrangian mass transport induced by the surface waves. Compared to the propagation in the absence of waves, the dynamics of the concentration field is governed by an enhancement of mixing process due to the orbital motion. Key Points: The front velocity is enhanced or decreased depending on the Lagrangian mass transport Concentration is influenced by shear (interface) and orbital motion (core) A simple linear model can predict front velocity with and without waves